An investigation into how the Olympic Games have impacted upon their host countries; focusing mainly the economic footprint that the Games leave behind. - Ripley, Claudia (2007)
The aim of this research project is to explore the different ways in which the Olympic Games affect their host countries, whether that is by bringing in foreign direct investment, providing jobs, improving infrastructure, or on the flip side, by causing unnecessary uproar such as providing the country with huge costs, unused state of the arts sporting venues once the Games have finished and taking funding from causes that may be deemed more deserving such as local hospitals, arts councils and education.